Peningkatan Pengetahuan Dan Keterampilan Petani Melalui Pelatihan Budidaya Tanaman Obat Tradisional Untuk Mendukung Pengembangan Pelayanan Kesehatan Tradisional Di Desa Ketewel - Putra, I Gede Yudiana; Daryaswanti, Putu Intan; Muryani, Ni Made Sri; Widyanata, I Komang Jerry; I Kadek Artawan; Pendet, Ni Made diah Pusparini (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2023)
Background: Non-communicable diseases, including hypertension and diabetes mellitus, remain major health concerns in Ketewel Village, Sukawati District, Gianyar Regency. Although the Family Medicinal Plants (TOGA) program has been introduced, its utilization remains limited due to insufficient community knowledge regarding medicinal plant cultivation and management. This community service program aimed to improve farmers' knowledge and skills in cultivating medicinal plants to support community-based traditional health services. Methods: The activity was conducted on June 15, 2021, involving five members of the Subak Juan farmer group. A participatory approach was implemented through medicinal plant cultivation training and field extension using lectures, discussions, demonstrations, and learning by doing. Knowledge was assessed using pre-test and post-test, while practical skills were evaluated through direct observation. Results: The participants' mean knowledge score increased from 68 before the training to 89 after the intervention. In addition, 80% of participants (4 out of 5) were able to correctly demonstrate medicinal plant cultivation techniques according to the recommended cultivation procedures. Conclusion: The combination of medicinal plant cultivation training and field extension effectively improved farmers' knowledge and practical skills. This program has the potential to support the development of community-based traditional health services through the sustainable utilization of medicinal plants.